The Duty to Protect the Right to Life - Šurlan, Tijana (NBP. Nauka, bezbednosti, policija, 2021)
The author analyses one aspect of the right to life - the duty to protect the right to life. That aspect is not encompassed in definitions of the right to life in clear and explicit words. However, it is elucidated through the process of interpretation by various bodies, both international and national. Explicit inclusion of this element is thoroughly analysed in General Comment No. 36 adopted by the UN Human Rights Committee and it presents the starting point for the analyses in this paper. The duty to protect the right to life has also been elaborated in specific cases before the UN Human Rights Committee, European Court of Human Rights and constitutional courts. Several of these cases have also been analysed within this paper. The aim of the paper is to identify the scope and limits of the duty to protect the right to life.
Keywords: the right to life, the duty to protect, UN Human Rights Committee, European Court of Human Rights, constitutional courts